Genomic Analysis of Antibiotic Resistance and Virulence Profiles in Escherichia coli Linked to Sternal Bursitis in Chickens: A One Health Perspective - Jessica Ribeiro; Vanessa Silva; Catarina Freitas; Pedro Pinto; Madalena Vieira-Pinto; Rita Batista; Alexandra Nunes; João Paulo Gomes; José Eduardo Pereira; Gilberto Igrejas; Lillian Barros; Sandrina A. Heleno; et al. (Veterinary Sciences, 2025)
Sternal bursitis is an underexplored lesion in poultry, often overlooked in microbiological diagnostics. In this study, we characterized 36 Escherichia coli isolates recovered from sternal bursitis in broiler chickens, combining phenotypic antimicrobial susceptibility testing, PCR-based screening, and whole genome sequencing (WGS). The genetic analysis revealed a diverse population spanning 15 sequence types, including ST155, ST201, and ST58. Resistance to tetracycline and ciprofloxacin was common, and several isolates carried genes encoding β-lactamases, including blaTEM-1B. Chromosomal mutations associated with quinolone and fosfomycin resistance (e.g., gyrA p.S83L, glpT_E448K) were also identified. WGS revealed a high number of virulence-associated genes per isolate (58–96), notably those linked to adhesion (fim, ecp clusters), secretion systems (T6SS), and iron acquisition (ent, fep, fes), suggesting strong pathogenic potential. Many isolates harbored virulence markers typical of ExPEC/APEC, such as iss, ompT, and traT, even in the absence of multidrug resistance. Our findings suggest that E. coli from sternal bursitis may act as reservoirs of resistance and virulence traits relevant to animal and public health. This highlights the need for including such lesions in genomic surveillance programs and reinforces the importance of integrated One Health approaches.